Solubility of SO2 in aqueous blend of sodium citrate and sodium hydroxide - Mondal M.K.; Chelluboyana V.R.; Rao J.S. (My University, 2025)
The solubility of SO2 in an aqueous blend of sodium citrate (Na3Ci) and sodium hydroxide (NaOH) as innovative absorbent was determined at partial pressures of SO2 in inlet gas stream between 0.355 kPa and 0.983 kPa, temperature between 293 K and 333 K, and NaOH to Na3Ci ratio in range of 0.25-1.00. The SO2 solubility was measured using laboratory scale bubble column at atmospheric pressure. From the experimental study low temperature, high partial pressure of SO2 in inlet gas stream and high NaOH to Na3Ci solution ratio were found favourable for SO2 solubility augmentation in aqueous blend of Na3Ci and NaOH. The experimental data were used to develop SO2 solubility model for suitability of the present system. © 2013 Elsevier B.V.